Hospitalization cost of Pressurized Intraperitoneal Aerosol chemotherapy (PIPAC). Issue 1 (January 2023) - Tidadini, Fatah; Ezanno, Anne-Cecile; Trilling, Bertrand; Aime, Adeline; Abba, Julio; Quesada, Jean-Louis; Foote, Alison; Chevallier, Thierry; Glehen, Olivier; Faucheron, Jean-Luc; Chkair, Sihame; Arvieux, Catherine
Abstract: Introduction: Pressurized Intraperitoneal Aerosol chemotherapy (PIPAC) is a new surgical technique for the treatment of unresectable peritoneal carcinomatosis. Very little data is available on the costs of this treatment in France as there is currently no code for PIPAC in the French Common Classification of Medical Acts (CCAM). Our objective was to estimate the mean cost of hospitalization for PIPAC in two French public teaching hospitals. Methods: The mean cost of hospitalization was estimated from the mean fixed-rate remuneration paid to the hospital and the mean additional costs of treatment paid by the hospital. At discharge a patient's hospitalization is classified into a diagnosis related group, which determines the fixed-rate remuneration paid to the hospital (obtained from the national hospitals database - PMSI). Costs of medical devices and drug treatments specific to PIPAC, not covered by the fixed-rate remuneration, were obtained from the hospital pharmacies. Results: Between July 2016 and November 2021, 205 PIPAC procedures were performed on 79 patients (mean procedures per patient = 2.6). Mean operating room occupancy was 165 min. The mean fixed-rate remuneration received by the hospitals per PIPAC hospitalization was €4031. The actual mean cost per hospitalization was €6562 for a mean length-of-stay of 3.3 days. Thus, each PIPAC hospitalization cost the hospital €2531 on average. Conclusion: The current reimbursement of PIPAC treatment by the national health system is insufficient and represents only 61% of the real cost. The creation of a new fixed-rate remuneration for PIPAC taking into account this cost differential is necessary.